Exploring the roles of citizens in performance measurement - Ho, Alfred T. (2007)
This article discusses why citizens should be involved in performance measurement of government and introduces a model of citizen-initiated performance assessment (CIPA). Based on the experiences of a few Iowa cities and a survey of Iowa local officials, it shows how citizen involvement has impacted the practice of performance measurement, increased the likelihood of integrating performance informa;tion in the decision-making and planning process by elected officials, stimulated different thinking about public service delivery, and opened up new opportunities to build a stronger partnership between the government and the citizenry. the article concludes by discussing the limitations of the Iowa experiment, an d suggests directions for future research and experimentation to advance the understanding and adoption of citizen-based performance measurement. - Reproduced.
Keywords: Performance appraisal